PERNIKAHAN ADAT JAWA DADUNG KEPUNTIR DALAM PERSPEKTIF MASLAHAH MURSALAH (STUDI KASUS DESA SEKAPUK KECAMATAN UJUNGPANGKAH KABUPATEN GRESIK) - Putri Nailatul Iqna’ah; Ahmad Subekti; Humaidi Humaidi (Jurnal Hikmatina, 2021)
In the view of Islam, marriage is to complete the worship of a Muslim. and in Islam, marriage can also make a partner capable of creating devout people in accordance with the values of goodness in Islam. Javanese traditions and customs are also not left behind in arranging a marriage in the Javanese community. As is the case with the Javanese tradition of Dadung Kepuntir in Sekapuk Village, Ujungpangkah District, Gresik Regency. This Javanese custom is a Javanese traditional marriage where two families marry brother to sister, while sister to brother. The marriage is an anticipatory step so that it does not occur in marriage. In this study, data collection uses three ways, namely, observation, interviews, and documentation. In The resullts of this study can be conclued that the Dadung Kepuntir marriage has been the belief of the local community since the time of their ancestors. Even though the entiire comunity of Sekapuk Vilage, Ujungpangkah District, Gresik Regency embraces Islam, the majority of peoplle are stil woried so much is being considered before getting married. Keywords: Marriage, Dadung Kepuntir Javanese custom, Maslahah Mursalah